Salivary cortisol measurements in brachycephalic dog breeds as part of a standardized stress test - Kähler, Elisa; Meyer-Lindenberg, Andrea; Zablotski, Yury; Schroers, Maike (Frontiers in Veterinary Science, 2024)
Brachycephalic obstructive airway syndrome (BOAS) is a common condition in brachycephalic dogs, with Pugs (PG) and French Bulldogs (FB) appearing to be particularly typically affected. Objective and easy-to-perform tests are necessary to detect the disease at an early stage and to exclude dogs affected by BOAS from breeding. The present study investigated the extent to which vital signs and salivary cortisol concentrations can be used to distinguish between healthy and BOAS-affected dogs in a standardised fitness test. A total of 57 PG, 56 FB and 27 meso-and dolichocephalic dogs were studied as control group (CG). In addition to vital signs, salivary cortisol concentrations were measured before and after the exercise test. It emerged that non-brachycephalic dogs showed a higher fitness level than brachycephalic dogs. The PG recovered significantly slower than the FB after the exercise test. In unaffected PG, cortisol levels rose significantly after the test and then fell again, in unaffected FB they fell significantly during the test. Unexpectedly, cortisol levels remained constant in BOAS affected dogs of both breeds. A possible explanation could be a disturbance of the pituitaryhypothalamic-adrenal axis, which could be due to the chronic stress of affected animals. This would have to be clarified in further studies. In conclusion, a submaximal fitness test may be a useful method to identify dogs suffering from BOAS as it is imperative to prevent the breeding and reproduction of affected dogs.